Respuesta agronómica y productiva de dos variedades de lechuga (Lactuca sativa L.), en asociación con espinaca (Spinacia oleracea), utilizando tres tipos de abonos orgánicos en la localidad de San Juan de Llullundongo, provincia Bolívar - Malca Lema, Vilma Yolanda (2023)
The present research work was established to evaluate the "Agronomic and productive response of two varieties of lettuce (Lactuca sativa L.), in association with spinach (Spinacia oleracea), using three types of organic fertilizers in the town of San Juan de Llullundongo, Bolivar province. The proposed objectives were: i) Identify the agronomic characteristics of the evaluated varieties. ii) Determine the chemical efficiency of the application of the three types of fertilizers. iii) Evaluate the response of the varieties under the application of fertilizers. iv) Establish the benefit-cost relationship of the different treatments. The treatments under study were for the FA two (lettuce varieties) for the FB three (organic fertilizers) and a control (without fertilization). The Randomized Complete Block Design (DBCA) was used with a 2 x 4 factorial system and 3 repetitions. The type of analysis that was carried out was Tukey's test at 5% to compare means of factor A and factor B and interaction of factors A x B when the Fisher is significant, correlation and Simple linear regression and analysis of the benefit relationship - cost. The variables were evaluated: Percentage of taking (PP), Plant height (AP), Number of leaves per plant (NHP), Days to cabbage formation (DFR), Days to harvest (DC), Number of plants harvested (NPC), Incidence of pests and diseases (IPE), Yield per plot (RP), Leaf weight (PH), Yield per hectare (RH). The statistical results show that the lettuce varieties in terms of yield, significantly depended on organic fertilizers, the treatments that obtained the highest yield average were: A1B3 (Iceberg + Gallinaza) with 24864.8 kg/ha and A1B2 (Iceberg + Worm humus) with 20620.3 kg/ha, while the lowest yield average was recorded in the controls (without fertilization) The variables: Engagement percentage (PP), Number of plants harvested (NPC) and Yield per plot (RP) were the components that contributed to increasing the yield of the lettuce varieties. The treatments that generated the highest economic income were: A1B3 (Iceberg + Gallinaza) with $6,216.20 and a profit of $0.49 and A2B3 (Batavia + Gallinaza) with $4,854.28, with a benefit/cost ratio of $0.16.